Analysis of Fatigue and Dehydration Risk Factors Among Hajj Pilgrims During Long Distance Travel: A Study on Hajj Pilgrims in 2025 - Putri, Sabila Rosyidah Wibawa; Griana, Tias Pramesti (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 3 (2025): Proceeding Annual Symposium on Hajj and Umrah MedicineDO - 10.18860/anshar.v3i0.3787, 2026)
Indonesian Hajj pilgrims face significant health risks due to fatigue and dehydration, particularly during the return phase (debarkation), which involves long distance travel, time zone changes, and extreme environmental conditions. This study aims to identify and explain the risk factors of fatigue and dehydration experienced by Hajj pilgrims during long distance travel, as well as their impact on pilgrims’ health, especially among the elderly. The results show that major risk factors include advanced age, prolonged travel duration, inadequate fluid intake, dry airplane cabin environment, non-ergonomic seating, comorbid diseases, sleep disturbances, and psychological and physical stress during transportation. Fatigue and dehydration are interrelated health problems that significantly affect the physical condition of pilgrims. Therefore, structured promotive and preventive efforts such as pre-departure education, proper hydration and rest management during travel, and logistical preparedness during the return phase are essential to reduce health risks and improve the well being of Hajj pilgrims.